Criminally Explosive: Intermittent Explosive Disorder, Criminal Careers, and Psychopathology among Federal Correctional Clients. Issue 4 (2nd October 2017) - DeLisi, Matt; Elbert, Michael; Caropreso, Daniel; Tahja, Katherine; Heinrichs, Timothy; Drury, Alan
ABSTRACT: Intermittent Explosive Disorder (IED) is a relatively rare psychiatric condition characterized by aggression, explosive outbursts towards people and property, and very poorly regulated emotional and behavioral control, but has rarely been studied in a criminal justice context. Drawing on data from 863 federal correctional clients from a supervised release population in the Midwestern United States, the current study examined the lifetime prevalence and correlates of IED and its associations with criminal careers. The lifetime prevalence of IED was 2.6% with another 1% of clients exhibiting symptoms of the disorder. Poisson and negative binomial regression models have shown that IED was significantly associated with arrests for murder, attempted murder, interference with police, aggravated assault, simple assault, and domestic assault despite controls for serious behavioral disorders, age of first arrest, and demographics. Clients with IED were also dramatically more likely to be habitual offenders and accumulate chronic arrests for assault-related crimes. These offenders pose considerable risk to staff safety and should be supervised with the highest level of supervision.